PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBANTUAN CANVA BERBASIS SEJARAH LOKAL “TENGKU AMIR HAMZAH” UNTUK SISWA KELAS IV SDN 056635 AIR HITAM - Lasmaida Br Siahaan, Theresia; aprillia, Rapita; Kumala Sari, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited integration of local history into Social and Natural Sciences (IPAS) learning at the elementary school level highlights the need for more contextual learning media. This Research and Development (R&D) study aims to develop Canva-assisted instructional video media based on the local history of Tengku Amir Hamzah, while also evaluating its validity and practicality. Utilizing the 4D development model (Define, Design, Develop, Disseminate), this research involved fourth-grade students at SDN 056635 Air Hitam as subjects. Data were collected through observation, interviews, documentation, and questionnaires. The validation results indicated that the developed media was categorized as